Genome-Wide Identification and Expression Analysis of Amino Acid/Auxin Permease (AAAP) Genes in Grapes (Vitis vinifera L.) Under Abiotic Stress and During Development - Xufeng Guo; Na He; Biying Huang; Chongyao Chen; Yanxia Zhang; Xiaoyu Yang; Jie Li; Zhigang Dong (Plants)
Amino acids in wine grapes function as precursors for various secondary metabolites and play a vital role in plant growth, development, and stress resistance. The amino acid/auxin permease (AAAP) genes encode a large family of transporters; however, the identification and function of the AAAP gene family in grapes remain limited. Consequently, we conducted a comprehensive bioinformatics analysis of all AAAP genes in grapes, encompassing genome sequence analysis, conserved protein domain identification, chromosomal localization, phylogenetic relationship analysis, and gene expression profiling. This study identified 60 VvAAAP genes, distributed on 14 chromosomes and classified into eight subfamilies. Microarray and transcriptome data revealed that most VvAAAP genes decrease during development, but VvAAAP7 and VvAAAP33 gradually increase. VvAAAP23 and VvAAAP46 exhibited significantly higher expression levels, while VvAAAP30 demonstrated lower expression when subjected to salt and drought stress. VvAAAP genes exhibited diverse expression patterns, suggesting that the AAAP gene family possesses both diversity and specific functions in grapes. Furthermore, the expression patterns of VvAAAP genes analyzed by RT-qPCR facilitate further investigation into the biological functions of individual genes in different tissues. These findings provide valuable insights into the continued analysis of the AAAP gene family’s functions in grapes.